Impact of 3D echocardiography on grading of mitral stenosis and prediction of clinical events. Issue 4 (December 2018) - Bleakley, C; Eskandari, M; Aldalati, O; Moschonas, K; Huang, M; Whittaker, A; Monaghan, M J
Abstract : Background: The mitral valve orifice area (MVOA) is difficult to assess accurately by 2D echocardiography because of geometric assumptions; therefore, 3D planimetry may offer advantages. We studied the differences in MVOA measurements between the most frequently used methods, to determine if 3D planimetry would result in the re-grading of severity in any cases, and whether it was a more accurate predictor of clinical outcomes. Methods: This was a head-to-head comparison of the three most commonly used techniques to grade mitral stenosis (MS) by orifice area and to assess their impact on clinical outcomes. 2D measurements (pressure half-time (PHT), planimetry) and 3D planimetry were performed retrospectively on patients with at least mild MS. The clinical primary endpoint was defined as a composite of MV balloon valvotomy, mitral valve repair or replacement (MVR) and/or acute heart failure (HF) admissions. Results: Forty-one consecutive patients were included; the majority were female (35; 85.4%), average age 55 (17) years. Mean and peak MV gradients were 9.4 (4) mmHg and 19 (6) mmHg, respectively. 2D and 3D measures of MVOA differed significantly; mean 2D planimetry MVOA was 1.28 (0.40) cm 2, mean 3D planimetry MVOA 1.15 (0.29) cm 2 ( P  = 0.003). Mean PHT MVOA was 1.43 (0.44) cm 2 ( P  = 0.046 and P  < 0.001 in comparison to 2D and 3D planimetry methods, respectively). 3D planimetry reclassified 7 (17%) patients from mild-to-moderate MS, and 1 (2.4%) from moderate to severe. Overall, differences between the two methods were significant ( X 2, P  < 0.001). Only cases graded as severe by 3D predicted the primary outcome measure compared with mild or moderate cases (odds ratio 5.7). Conclusion: 3D planimetry in MS returns significantly smaller measurements, which in some cases results in the reclassification of severity. Routine use of 3D may significantly influence the management of MS, with a degree of prediction of clinical outcomes.